Effect of Product Quality, Promotion and Personal Selling on Purchase Decisions Through Intention to Buy Amazink Ink Consumers in Cirebon City - Fandi Mardyono; Kumba Digdowiseiso (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study seeks to examine the direct and indirect effects of product quality, promotion, and personal selling on the purchase intention and purchasing decisions of Cirebon City Amazink ink consumers. Using STATA Version 14, data from 154 respondents were processed utilizing the path analysis methodology. The results demonstrated that product quality, promotion, and personal selling had a positive and statistically significant effect on consumer purchasing interest. In addition, these factors have a positive and substantial impact on the purchasing decisions of consumers. However, there was no significant correlation between purchase intent and purchase behavior. The results of the mediation analysis indicate that consumer buying interest partially mediates the influence of product quality, promotion, and personal selling on purchasing decisions.